Analisis Tingkat Kepuasan Masyarakat terhadap Penerapan Generator-Mikrohidro sebagai Sumber Energi Listrik di Dusun Batu Saeng, Lampung - Madi Madi; Khoirun Naimah; Duwi Hariyanto; Rinaldi Ikhram; Isnaini Rahmadi; Alfajar Puja Kusuma; Hasbiyalloh Hasbiyalloh; Risfihan Rafi (Universitas Mathla'ul Anwar Banten, 2021)
ANALYSIS OF THE LEVEL OF COMMUNITY SATISFACTION ON THE APPLICATION OF MICRO-HYDRO GENERATORS AS A SOURCE OF ELECTRICAL ENERGY IN BATU SAENG, LAMPUNG. Generator-Micro hydro is a very important component for hydroelectric power in meeting the electricity needs of the community. Batu Saeng is one of the areas in Lampung Province that still lacks electricity. The people there are always hydropower. However, based on a team survey, several components are no longer suitable for use, one of which is a generator. This old generator with a capacity of 8000 watts has been used by the people of Batu Saeng, but its condition is currently rusty, almost burnt, and is no longer suitable for use. This condition is due to economic problems that make it impossible to replace micro-hydro plants. Therefore, the community service team helped replace a newer generator with a larger capacity of 10,000 watts. A 10,000 watt micro hydro power plant has supplied electricity to 20 houses in Batu Saeng. The community service team also obtained data from the community satisfaction survey on the application of the 10,000 watt micro hydro generator. The scope consists of administration, procedures, communication, engineering, and generating equipment. The analysis results show that 100% of the people are very satisfied with the implementation of the micro hydro generator by the service team.